1987
DOI: 10.1080/09553008714550761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ionizing Radiation on Artificial (Planar) Lipid Membranes. I. Radiation Inactivation of the Ion Channel Gramicidin A

Abstract: The ion channel formed by the pentadecapeptide gramicidin A in planar lipid membranes is extremely sensitive to ionizing radiation. The membrane conductance may drop by several orders of magnitude under appropriate experimental conditions (low pH and presence of oxygen). The radiation sensitivity is strongly reduced for gramicidin M-. This analogue has the four tryptophan residues replaced by phenylalanines. Experiments performed in the presence of various radical scavengers suggest that the inactivation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The time constants for both exponentials varied approximately in proportion to the number of Trps present, consistent with the concept that photolysis of any one of the Trps inactivates the channel. Similar results were found with ionizing X irradiation (149,150), although the mechanism was shown to involve the reaction of free radicals with the Trps. Neither UV-nor X-irradiation are effective with gramicidin M-, which contains Phe in place of each Trp.…”
Section: Radiol Ysis and Photolysissupporting
confidence: 87%
“…The time constants for both exponentials varied approximately in proportion to the number of Trps present, consistent with the concept that photolysis of any one of the Trps inactivates the channel. Similar results were found with ionizing X irradiation (149,150), although the mechanism was shown to involve the reaction of free radicals with the Trps. Neither UV-nor X-irradiation are effective with gramicidin M-, which contains Phe in place of each Trp.…”
Section: Radiol Ysis and Photolysissupporting
confidence: 87%
“…Experiments using different radical scavengers [35] have indicated that channel inactivation by radiolysis is due to a subsequent reaction of OH and HO 2 radicals with Trp residues of gA. Ethanol is frequently used to chemically block some species of free radicals produced by irradiation [22]. In our experiments a concentration of 10% of ethanol in the buffer used to prepare the liposomes almost completely prevented the effect of irradiation, in good agreement with the results of Bonnefont-Rousselot et al [22].…”
Section: Discussionsupporting
confidence: 90%
“…Another phenomenon associated with radiation-induced lipid peroxidation was the increase of membrane capacitance [18] explained in terms of increase of the membrane dielectrical constant. This small change of the dielectrical constant can be the cause of the large increase in membrane conductance in the presence of macrocyclic ion carriers of the valinomycin type [35].…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation may result from a chemical reaction with free radicals generated by water radiolysis. The membrane conductance induced by gramicidin A is reduced by many orders of magnitude by a reaction of OH and of HO; radicals with the tryptophan residues of the peptide (7)(8)(9). The hydroxyl radical OH' and the perhydroxyl radical Ho2 (as well as other oxygen radicals) are well known for their deleterious cellular effects and have been discussed in the context with a variety of diseases ( 10).…”
Section: Introductionmentioning
confidence: 99%
“…Average dose rates (including the repetition time) of up to 104 Gy/min were used. For further details of the method of pulse radiolysis (as applied at planar lipid membranes) the reader should consult references (8) and ( 12).…”
mentioning
confidence: 99%